Hout Bay: a developmental strategy - Bisset, Ronald (School of Architecture, Planning and Geomatics, 2020)
The Hout Bay Valley, surrounded by mountains and the Atlantic Ocean, is a unique ecological entity operating within the wider Metropolitan context of Cape Town. Sited as it is on the fringe of the expanding urban periphery of Cape Town, it is a beautiful legacy, a serious responsibility, an area of challenge and opportunity, and an area threatened by an uncontrolled residential expansion and concomitant sub-division and exploitation of farmlands for ancillary urban related facilities, which factor is eroding, and threatening to destroy, the rustic environmental qualities of the Valley by an industrial expansion in the harbour enclave which could disturb the delicate balance within the Valley.